Multiple-Project Financing with Informed Trading - Salvatore Cantale; Dmitry Lukin (The Journal of Entrepreneurial Finance (JEF), 2012)
The paper presents an adverse selection-based explanation of the fact that some entrepreneurs choose to finance multiple projects together by issuing a single security and other entrepreneurs decide to finance each project separately. We consider the financing problem of an entrepreneur who has access to two investment projects and needs to raise external financing to undertake these projects in the presence of asymmetric information. The entrepreneur has private information about the quality of the projects and can choose either to finance the projects together by issuing a single security, or to finance the projects separately by issuing two securities, each backed by the cash flows from the corresponding projects. We show that the choice of financing depends on the structure of information available to outside investors. If there are two types of informed traders and each type knows the true value of a different project, the entrepreneur will always choose to finance projects separately. However, if there is only one type of informed trader in the market and she has information about the true value of both projects, then the entrepreneur may, in some circumstances, resort to joint financing.
Keywords: D81; G31; G32; M13; 650; Capital Budgeting; Adverse Selection; Outside Investment; Entrepreneur